PEMANFAATAN SERBUK GERGAJI SEBAGAI BAHAN BAKU BRIKET - Pratiwi Nova Sari; Sitti Aminah (Universitas Tadulako, 2020)
Wood sawdust is one of the wastes from wood processing industry such as sawdust and peel residues. They are cheap raw materials and potential as a source of alternative energy by processing it into charcoal briquettes. The use of charcoal briquettes as a substitute for fossil energy sources has several advantages including the relatively less smoke emitted because it has been released during the carbonization process. They can be stored for a long time and the calor value is higher than wood. Charcoal briquettes are made from wood sawdust which is added by tapioca flour as glue. This study was conducted in two main stages, processing charcoal briquette and characterization. The characterization of charcoal briquettes are including density, moisture, ash, volatile substances levels, carbon bound, long flame and calor value. The results obtained from the charcoal briquettes are a density of 0.384 gr/cm3, a moisture of 2.44%, an ash of 4.82%, a volatile substance of 19.13%, a carbon bond of 74.44%, a briquette flame of 6.75 minutes/gr and the calor value of 5127 cal/gr. This study concluded that wood sawdust briquette has the potential to be used potentially as substitued for fuel.